Ibuprofen on Proliferation and Apoptosis of Sarcoma Cells via PI3K/Akt/mTOR Signaling Pathway - Bai, Ye; Guo, Ning; Chen, Qinghe; Chen, Yuxi; Bi, Zhenggang (Cellular and Molecular Biology, 2022)
Nowadays, there is a serious lack of information about the value-added apoptosis of sarcoma cells in China. Especially in clinical medicine, exploring the effect of ibuprofen on the growth and apoptosis of fibrosarcoma cells under the PI3K/Akt/mTOR signaling pathway can not only effectively prevent us in advance, but also be a great way to break through this field. The main purpose of this study was to investigate the effects of ibuprofen on the proliferation, cell cycle and apoptosis of fibrosarcoma cells through the PI3K/Akt/mTOR signaling pathway. We divided the HTl080 cell line into zero control group, control group and experimental group. The withering group was not inoculated with any cells, while the control group was only added with the same amount of culture medium, while the experimental group was added with 5,10,15,20 concentrations respectively. We found that the apoptosis rate of sarcoma cells in the control group increased from 5.66% to 7.12%, while the apoptosis rate of sarcoma cells in the experimental group increased significantly faster than that in the control group, with an overall increase of 7.16%, from 4.56% to 11.72%. Therefore, we can be surer that ibuprofen has a very good inhibitory effect on the proliferation, cell cycle and apoptosis of fibrosarcoma cells under the PI3K/Akt/mTOR signaling pathway. Therefore, when ibuprofen was injected into the body, it could not only observe the sarcoma cells well but also reflect the good inhibitory effect of ibuprofen on other substances in vivo under the PI3K/Akt/mTOR signaling pathway.